Uridine triacetate for severe 5-fluorouracil toxicity in a patient with thymidylate synthase gene variation: Potential pharmacogenomic implications. (30th June 2018) - Baldeo, Candice; Vishnu, Prakash; Mody, Kabir; Kasi, Pashtoon Murtaza
Adverse drug reactions can be unpredictable. However, pharmacogenomic testing can help identify patients who may be more susceptible to the toxic effects of certain drugs. Genetic variations in the dihydropyrimidine dehydrogenase and thymidylate synthase genes have been shown to increase the risk of 5-fluorouracil toxicity. 5-Fluorouracil toxicity can be life threatening. Fortunately, there is treatment available for 5-fluorouracil toxicity, called uridine triacetate. Although, the indications for its use limit its administration to within 96 h of receiving 5-fluorouracil, we report a case of effective therapy in a patient started on uridine triacetate beyond the recommended 96 h, who was found to carry a thymidylate synthase gene variation but no dihydropyrimidine dehydrogenase mutations. This provides important implications for pharmacogenomic testing.